Perancangan Flexible Exhibition Stand dengan Material Cardboard - Gunawan, Silvia (Intra, 2015)
Cardboard is a material that is used to make packagings with limited lifetime in the distribution process of a product to the consumer. Cardboard is made by recycling waste paper to an innovative product which increases the value of it. The design of flexible exhibition stand is an innovation that uses cardboard material in order to make the assembly of the exhibition stand easier for the exhibitor, and the process is done only in a short time. Knock-down construction method is used by folding and interlocking. The design consists of space-forming, space-filling, and exhibition decorative elements. The advantages of using cardboard for exhibition are less production cost, abundant source of raw materials, lighter, self-assembly without tools, flexible with the condition and the area of exhibition space, strength that can replace the lumber construction in resisting the load.